LINGKUNGAN BARU: ADAPTASI BUDAYA OLEH DOSEN CPNS - Wiradharma, Gunawan (Master of Communication Science Program, Universitas Diponegoro, 2020)
CPNS lecturers in 2019 at Universitas Terbuka were placed in the head office or in various UPBJJ spreading throughout Indonesia. Some CPNS lecturers are placed in different units from their original regions so they have to make adjustments in the new environments with different cultures. Intercultural communication takes place when there is interaction between an individual with a particular cultural background and other individuals who come from different cultures. Intercultural communication is an important key in the adjustment process. This study explores the adaptation of three UT CPNS lecturers from outside the region. The theory used is Anxiety Uncertainty Management Theory. Descriptive qualitative approach is used to explore the perspective of CPNS lecturers with the local culture. Through this research, the researcher found that there were some important elements that needed to be possessed by CPNS lecturers, namely the cultural adaptation that was carried out, the culture shock that occurred, and the adjustment in the new cultural environment.